مراعاة المصلحة في التمويل بالقرض الحسن في البنوك الإسلامية: بنك البركة الجزائري نموذجًا = Consideration of public interest (Maṣlaḥah) in al-Qarḍ Al-Ḥasan financing in Islamic banks: a case study of Al Baraka Bank of Algeria - Arif, Arif Ali; Ahmed Bourkab, Mohammed; Hendaoui, Hassan Ben Brahim; Kouadri, Missou (IIUM Press, International Islamic University Malaysia, 2019)
لقد اتفق علماء الأمة و فقهاؤها عبر عصور التشريع الإسلامي على كون المقصد الأسمى من الشريعة الإسلامية هو رعاية مصالح الخلق بجلب المصلحة لهم أو درء المفسدة عنهم، وتنوعت تعبيراتهم عن المصلحة، وضوابطهم في الأخذ بها، ويأتي هذا البحث لبيان مفهوم المصلحة بصفة عامة والمصلحة المرسلة بصفة الخاصة . وحيث أن دليل المصلحة هو الأصل الذي تبنى عليه أحكام المعاملات المالية، والمصرفية فسيتناول بعض المسائل في مراعاة المصلحة في التمويل بالقرض الحسن في المصارف الإسلامية ومناقشة آراء الفقهاء حولها، بالإضافة إلى بيان إجراءات منح القرض الحسن في بنك البركة الإسلامي بالجزائر، وإبراز بيان مدى حاجة فئة الشباب الجزائري الحصول على القرض الحسن من خلال توزيع استبيانات بين أفراد هذه الفئة. ********************************************************************************* The ultimate purpose of Sharia law is to protect the welfare of humans by bringing benefits for them and preventing harms from them. The jurists agree that the evidence of maslahah is the basis on which the provisions of financial and banking transactions are based regardless of their difference of opinions in terms of its conditions. The reality of Islamic banking transactions and the complexity of many of its issues make the existence of clear evidence from the Quran and Sunnah difficult, which necessitates for the researchers to make additional efforts in this field, and conduct ijtihad to use the evidence of maslahah with its legal conditions as a way to reveal the Shari`ah rulings by following the Companions and righteous scholars during their time. Therefore, the research will deal with the concept of maslahah and some issues related to considering it in financing with al-Qarḍ al-Ḥasan in the Islamic banks, and opinions of scholars about it. In addition, it explains the procedures of granting al-Qarḍ al-Ḥasan at Al Baraka Islamic Bank in Algeria and highlights the need of the Algerian youth to obtain al-Qarḍ al-Ḥasan which will be investigated through the distribution of questionnaires among them. The research follows the inductive approach to extrapolate the scholars' opinions, and analytic approach to analyze their views, and analyze the results of the questionnaires about al-Qarḍ al-Ḥasan. The research concludes that the Shari`ah ruling of some issues of al-Qarḍ al-Ḥasan is based on evidence of maslahah including all of its types which are considered, canceled and silenced ones.